2011
DOI: 10.1109/mis.2011.75
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Gap: Face-to-Face Negotiations with an Automated Mediator

Abstract: Abstract-Mediation is an important paradigm for dispute resolution. It can lead to "win-win" situations and benefit all parties. Yet, when people negotiate they demonstrate bounded rationality in their actions and diversity in their behaviors. This increases the difficulty to design automated mediators. To be successful, the mediator must take this into account and propose solutions deemed relevant, otherwise it will lose the focus and trust of the negotiators. To tackle these difficulties we present AniMed -a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…Online conflict resolution courses are now offered in a variety of academic institutions (Bhappu, Ebner, Kaufman, & Welsh, 2010;Ebner, 2008;Matz & Ebner, 2010). E-negotiation and e-mediation systems are made available in order to help negotiators satisfy their requirements and to assist them in negotiations (Druckman et al, 2011;Druckman, Druckman, & Arai, 2004;Lin, Gev, & Kraus, 2011). Technology becomes prevalent in the use of decision support systems in negotiation simulations (Wilkenfeld, Young, Queen, & Assal, 2005) and web-based simulation programs like GlobalEd Gehlbach et al, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Online conflict resolution courses are now offered in a variety of academic institutions (Bhappu, Ebner, Kaufman, & Welsh, 2010;Ebner, 2008;Matz & Ebner, 2010). E-negotiation and e-mediation systems are made available in order to help negotiators satisfy their requirements and to assist them in negotiations (Druckman et al, 2011;Druckman, Druckman, & Arai, 2004;Lin, Gev, & Kraus, 2011). Technology becomes prevalent in the use of decision support systems in negotiation simulations (Wilkenfeld, Young, Queen, & Assal, 2005) and web-based simulation programs like GlobalEd Gehlbach et al, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most of the research on web-based and digital technologies in teaching and learning (Hannafin & Kim, 2003;Lawless & Brown, 2003) focus on innovations in using the World Wide Web in teaching in general rather than focusing on computer games in a conflict resolution context. Few studies (Chalamish & Kraus, 2012;Lin et al, 2011) have systematically analyzed the effects of technology support as opposed to no technology support in negotiation simulations like PeaceMaker. Some argue that face-to-face negotiation has many advantages over e-negotiation; others think the opposite (Galin, Gross, & Gosalkler, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the GENIE and Pocket Negotiator projects [44,45] focused on how to use an agent as decision support during a person's negotiation session. AutoMed and AniMed* are agents that act as a mediator between bilateral negotiations between people [46,47]. An important open question is if or how NegoChat-A's strategy could be changed for decision support or mediation.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…The mediator in the study was based on AutoMed (Chalamish & Kraus, ), an automated mediator shown to produce better settlement rates, faster settlements, and greater negotiator satisfaction than unmediated negotiations; the AutoMed mediator was then adapted to program the manipulative mediator used in the current study (see details of the agent design in Lin et al, ). The agent mediator in both conditions was programmed to maximize the social welfare of the participants' agreement.…”
Section: Methodsmentioning
confidence: 99%